Mapping Ten Years of Digital Burnout Research (2015–2024): a Scopus-Based Bibliometric Analysis - Rima Febrianti; Pieter Andrian; Reni Januarti; Sri Astuti Handayani; Tatan Mayandripan (Ilomata International Journal of Social Science, 2026)
This study investigates the evolution of research on digital burnout and digital stress by applying a systematic bibliometric approach to publications indexed in Scopus between 2015 and 2024. The objective is to identify publication trends, intellectual structures, and emerging thematic patterns within this domain. A structured search strategy was implemented using predefined keywords, followed by a screening process based on relevance, document type, and duplication removal, resulting in a final sample of 162 peer-reviewed articles. Bibliometric analysis was conducted using VOSviewer and Bibliometrix to perform co-authorship, co-occurrence, and citation network analyses. The findings indicate a marked increase in publication output after 2020, reflecting intensified scholarly attention during the global digital transition period. Network visualization reveals that research is concentrated around three dominant clusters: (1) psychological impacts of digital overload, (2) organizational and occupational stressors linked to constant connectivity, and (3) coping mechanisms including digital detox and boundary management. Germany emerges as a central contributor in terms of institutional productivity and collaboration networks. Additionally, keyword co-occurrence analysis highlights a recent shift toward hybrid work environments and techno-stress mitigation strategies. This study contributes by providing a structured mapping of the intellectual and thematic evolution of digital burnout research, emphasizing the transition from individual-level analysis to organizational and systemic perspectives. The results offer an evidence-based foundation for future research directions, particularly in refining conceptual frameworks and identifying underexplored areas such as long-term adaptation to digital work ecosystems.